Association between age at first birth and risk of rheumatoid arthritis in women: Evidence from NHANES 2011–2020 - Hang Cui; Chenyang Huang; Yuntian Ye; Tianci Guo; Weijie Yu; Puyu Niu; Kuiliang Gao; Jiajin Liu; Aifeng Liu (PLoS ONE, 2025)
Objective This study focused on investigating the relation of age at first birth (AFB) with rheumatoid arthritis (RA) risk in women based on the 2011–2020 NHANES (National Health and Nutrition Examination Survey) data. Methods Women were analyzed using National Health and Nutrition Examination Survey (NHANES) data from 2011 to 2020 in the US. Both AFB and RA diagnoses were obtained through self-reported questionnaires. Odds ratios (ORs) and 95% confidence intervals (CIs) were determined using logistic regression models. Results Among the 7,449 women included in this study, 552 (7%) were diagnosed with RA. In comparison with women who had an AFB of 30–32 years (reference group), those who had an AFB < 18, 18–20, 21–23, 24–26, and > 35 years had the fully adjusted ORs and 95% CIs of 4.00 (95% CI 1.70, 9.40), 2.90 (95% CI 1.25, 6.73), 3.00 (95% CI 1.32, 6.80), 3.18 (95% CI 1.36–7.42), and 3.36 (95% CI 1.04–10.7), respectively. Due to the limitations inherent in cross-sectional studies, we have not observed significant differences in the risk of RA between women aged 27–29 and 33–35 at the AFB. Further research is warranted to refine these findings. Conclusion Women with an AFB < 26, or > 35 years have a higher risk of developing RA later in life. Policymakers may consider focusing more on women in these AFB age ranges in screening RA and making preventive measures.